Hierarchy based 3D Visualization of Large Software Structures - Michael Balzer; Oliver Deussen (Visualization'04: Poster Compendium of the IEEE Visualization Conference, 2004)
Modern object-oriented programs are hierarchical systems with many thousands of interrelated subsystems. Visualization helps developers to better comprehend these large and complex systems. This work presents a three-dimensional visualization technique that represents the static structure of object-oriented software using distributions of three-dimensional objects on a two-dimensional plane. The visual complexity is reduced by adjusting the transparency of object surfaces to the distance of the viewpoint. An approach called Hierarchical Net is proposed for a clear representation of the relationships between the subsystems.